Radon Gas Estimation from Building Materials - Caner Yalçın; Safa Başdemir (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Radon gas originating from building materials is generally thought to cause low concentration. Investigation and estimation of radon levels originating from building materials are important in terms of public health due to the use of dense concrete in tunnel form type houses, which is a building type widely used in Turkey, even though a significant part of Turkey is an earthquake zone. In this article, the effects of different parameters such as 238U concentration in building materials, diffusion constant of building elements, emanation rate, and ventilation rate on radon gas concentration are investigated. As a result, it is concluded that in some cases (such as high diffusion coefficient and insufficient ventilation rate) in houses built with tunnel form concrete structures, the radon level arising from building materials can reach a level that cannot be neglected.